1994
DOI: 10.1093/ejo/16.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial morphology in patients with multiple congenitally missing permanent teeth

Abstract: The purpose of this study was to examine the association between the number of congenitally missing permanent teeth, excluding third molars, and the craniofacial morphology. The sample comprised 118 children with five or more congenitally missing teeth. Twenty-seven reference points were digitized from lateral cephalometric radiographs and 13 angular measurements of craniofacial morphology were calculated. After an initial analysis, the sample was divided into two subsamples, one with 5-12 missing teeth and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
83
1
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 0 publications
12
83
1
9
Order By: Relevance
“…Nevertheless, severity of hypodontia may have a stronger association with vertical skeletal characteristics. Nodal et al (1994) observed significantly smaller mandibular plane angle, and gonial angle in a group of children with more than 12 teeth missing compared to that with 5-12 missing teeth (18). In addition, reduced vertical facial dimension and mandibular plane angle were observed in bilateral maxillary lateral agenesis cases by Woodworth et al (1985) (10).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, severity of hypodontia may have a stronger association with vertical skeletal characteristics. Nodal et al (1994) observed significantly smaller mandibular plane angle, and gonial angle in a group of children with more than 12 teeth missing compared to that with 5-12 missing teeth (18). In addition, reduced vertical facial dimension and mandibular plane angle were observed in bilateral maxillary lateral agenesis cases by Woodworth et al (1985) (10).…”
Section: Discussionmentioning
confidence: 86%
“…Some polygenic inheritance on formation of third molar germs suggested to be related to genes that control maxillary and/or mandibular dimensions8. De Coster et al (2009) stated that the list of genes involved in human non-syndromic hypodontia includes those encoding a signaling molecule (TGFA), and transcription factors (MSX1 and PAX9) that play critical roles during early craniofacial development (19). To our opinion, apart from genetic coding, higher frequency of third molar agenesis in retrognathic jaw morphology, may be as a result of influence of the presence of tooth germs in the bone on the growth and development of the jaws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have observed that increasing numbers of missing teeth results in a decrease in the mandibular plane angle and a reduction in facial height 9,10 . According to the findings from the lateral cephalometric analysis, and clinical finding, vertical dimension of occlusion was restored with an occlusal appliance therapy for better aesthetics and function before the construction of the fixed prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examining a relationship between missing teeth and skeletal pattern 9,10 revealed that, while increasing number of missing teeth results in a decrease in the mandibular plane angle, a reduction in facial height results in a less aesthetic facial appearance. Therefore, oligodontia associated with or without syndromes results in not only functional but also psychosocial problems, especially for young people 5,11 .…”
Section: Introductionmentioning
confidence: 99%